Association between thyroid hormones and TRAIL. - Bernardi, Stella; Bossi, Fleur; Toffoli, Barbara; Giudici, Fabiola; Bramante, Alessandra; Furlanis, Giulia; Stenner, Elisabetta; Secchiero, Paola; Zauli, Giorgio; Carretta, Renzo; Fabris, Bruno (Clin Biochem, 2017)
INTRODUCTION: Recent studies suggest that a circulating protein called TRAIL (TNF-related apoptosis-inducing ligand) might have a role in the regulation of body weight and metabolism. Interestingly, thyroid hormones seem to increase TRAIL tissue expression. This study aimed at evaluating whether overt thyroid disorders affected circulating TRAIL levels. METHODS: TRAIL circulating levels were measured in euthyroid, hyperthyroid, and hypothyroid patients before and after thyroid function normalization. Univariate and multivariate analyses were performed to evaluate the correlation between thyroid hormones and TRAIL. Then, the stimulatory effect of both triiodothyronine (T3) and thyroxine (T4) on TRAIL was evaluated in vitro on peripheral blood mononuclear cells. RESULTS: Circulating levels of TRAIL significantly increased in hyperthyroid and decreased in hypothyroid patients as compared to controls. Once thyroid function was restored, TRAIL levels normalized. There was an independent association between TRAIL and both fT3 and fT4. Consistent with these findings, T3 and T4 stimulated TRAIL release in vitro. CONCLUSION: Here we show that thyroid hormones are associated with TRAIL expression in vivo and stimulate TRAIL expression in vitro. Given the overlap between the metabolic effects of thyroid hormones and TRAIL, this work sheds light on the possibility that TRAIL might be one of the molecules mediating thyroid hormones peripheral effects.
Keywords: Aged; Female; Gene Expression Regulation; Humans; Hyperthyroidism; Hypothyroidism; Leukocytes, Mononuclear; Male; Middle Aged; Thyroxine; TNF-Related Apoptosis-Inducing Ligand; Triiodothyronine

Circulating osteoprotegerin is associated with chronic kidney disease in hypertensive patients. - Bernardi, Stella; Toffoli, Barbara; Bossi, Fleur; Candido, Riccardo; Stenner, Elisabetta; Carretta, Renzo; Barbone, Fabio; Fabris, Bruno (BMC Nephrol, 2017)
BACKGROUND: Osteoprotegerin (OPG) is a glycoprotein that plays an important regulatory role in the skeletal, vascular, and immune system. It has been shown that OPG predicts chronic kidney disease (CKD) in diabetic patients. We hypothesized that OPG could be a risk marker of CKD development also in non-diabetic hypertensive patients. METHODS: A case-control study was carried out to measure circulating OPG levels in 42 hypertensive patients with CKD and in 141 hypertensive patients without CKD. A potential relationship between OPG and the presence of CKD was investigated and a receiver-operating characteristic (ROC) curve was designed thereafter to identify a cut-off value of OPG that best explained the presence of CKD. Secondly, to evaluate whether OPG increase could affect the kidney, 18 C57BL/6J mice were randomized to be treated with saline or recombinant OPG every 3 weeks for 12 weeks. RESULTS: Circulating OPG levels were significantly higher in hypertensive patients with CKD, and there was a significant inverse association between OPG and renal function, that was independent from other variables. ROC analysis showed that OPG levels had a high statistically predictive value on CKD in hypertensive patients, which was greater than that of hypertension. The OPG best cut-off value associated with CKD was 1109.19 ng/L. In the experimental study, OPG delivery significantly increased the gene expression of pro-inflammatory and pro-fibrotic mediators, as well as the glomerular nitrosylation of proteins. CONCLUSIONS: This study shows that OPG is associated with CKD in hypertensive patients, where it might have a higher predictive value than that of hypertension for CKD development. Secondly, we found that OPG delivery significantly increased the expression of molecular pathways involved in kidney damage. Further longitudinal studies are needed not only to evaluate whether OPG predicts CKD development but also to clarify whether OPG should be considered a risk factor for CKD.
Keywords: Aged; Animals; Biomarkers; Case-Control Studies; Female; Follow-Up Studies; Humans; Hypertension; Male; Mice; Mice, Inbred C57BL; Middle Aged; Osteoprotegerin; Random Allocation; Renal Insufficiency, Chronic

Osteoprotegerin increases in metabolic syndrome and promotes adipose tissue proinflammatory changes. - Bernardi, Stella; Fabris, Bruno; Thomas, Merlin; Toffoli, Barbara; Tikellis, Christos; Candido, Riccardo; Catena, Cristiana; Mulatero, Paolo; Barbone, Fabio; Radillo, Oriano; Zauli, Giorgio; Secchiero, Paola (Mol Cell Endocrinol, 2014)
BACKGROUND: Inflammation is believed to link obesity to insulin resistance, as in the setting of metabolic syndrome (MetS). Osteoprotegerin (OPG) is a soluble protein that seems to exert proatherogenic and prodiabetogenic effects. This study aims at determining OPG levels in MetS and whether OPG might contribute to MetS development and progression. METHODOLOGY/PRINCIPAL FINDINGS: Circulating OPG was measured in 46 patients with MetS and 63 controls, and was found significantly elevated in those with MetS. In addition, circulating and tissue OPG was significantly increased in high-fat diet (HFD) fed C57BL6 mice, which is one of the animal models for the study of MetS. To evaluate the consequences of OPG elevation, we delivered this protein to C57BL6 mice, finding that it promoted systemic and adipose tissue proinflammatory changes in association with metabolic abnormalities. CONCLUSIONS/SIGNIFICANCE: These data suggest that OPG may trigger adipose tissue proinflammatory changes in MetS/HFD-induced obesity.
Keywords: Adipose Tissue; Adult; Animals; Blood Glucose; Body Mass Index; C-Reactive Protein; Case-Control Studies; Cholesterol, HDL; Cholesterol, LDL; Diet, High-Fat; Female; Humans; Inflammation; Insulin; Insulin Resistance; Male; Metabolic Syndrome X; Mice; Mice, Inbred C57BL; Middle Aged; Obesity; Osteoprotegerin; Triglycerides

Patients affected by metabolic syndrome show decreased levels of circulating platelet derived growth factor (PDGF)-BB. - Tisato, Veronica; Toffoli, Barbara; Monasta, Lorenzo; Bernardi, Stella; Candido, Riccardo; Zauli, Giorgio; Secchiero, Paola (Clin Nutr, 2013)
BACKGROUND & AIMS: The development and/or progression of metabolic syndrome (MetS) in overweight and obese individuals have been associated to low-grade inflammation, but few studies have simultaneously analyzed the circulating levels of several cytokines. METHODS: In this pilot study, a group of 27 cytokines and growth factors was analyzed in the serum of obese patients (n=40) diagnosed for MetS in comparison with sex- and age-matched control subjects without MetS (n=53) by using a multiplex immunoassay. Release of cytokines was measured in culture supernatants of human primary endothelial cells, THP-1 macrophagic cells and HuH-7 hepatoma cells upon exposure to a high fat mixture. RESULTS: While the majority of cytokines did not show significant differences between the investigated groups, the circulating levels of CXCL10/IP-10 and IL-6 were higher in the MetS group versus overweight control group. In contrast, PDGF-BB serum levels were significantly decreased in MetS patients. The in vitro addition of a high fat mixture increased the release of IL-6 and/or CXCL10/IP-10 in the culture supernatant of human primary endothelial cells and THP-1 macrophagic cells, while the same mixture significantly decreased the release of PDGF-BB by human THP-1 macrophagic and HuH-7 hepatoma cells. CONCLUSIONS: The current demonstration that MetS is associated with decrease of the pro-fibrotic PDGF cytokine is a completely novel finding, which adds complexity to the interplay between inflammation and fibrosis in patients affected by MetS.
Keywords: Adolescent; Adult; Aged; Case-Control Studies; Cell Line, Tumor; Chemokine CXCL10; Endothelial Cells; Female; Humans; Interleukin-6; Linear Models; Male; Metabolic Syndrome X; Middle Aged; Obesity; Pilot Projects; Proto-Oncogene Proteins c-sis; RNA, Messenger; Young Adult

Potential role of TRAIL in the management of autoimmune diabetes mellitus. - Bernardi, Stella; Norcio, Alessia; Toffoli, Barbara; Zauli, Giorgio; Secchiero, Paola (Curr Pharm Des, 2012)
Type 1 diabetes mellitus (T1DM) is an autoimmune disease, due to the immune-mediated destruction of pancreatic β-cells, whose incidence has been steadily increasing during the last decades. Insulin replacement therapy can treat T1DM, which, however, is still associated with substantial morbidity and mortality. For this reason, great effort is being put into developing strategies that could eventually prevent and/or cure this disease. These strategies are mainly focused on blocking the immune system from attacking β-cells together with functional islet restoration either by regeneration or transplantation. Recent experimental evidences suggest that TNFrelated apoptosis-inducing ligand (TRAIL), which is an immune system modulator protein, could represent an interesting candidate for the cure for T1DM and/or its complications. Here we review the evidences on the potential role of TRAIL in the management of T1DM.
Keywords: Animals; Autoimmunity; Diabetes Mellitus, Type 1; Humans; Hypoglycemic Agents; Insulin; Insulin-Secreting Cells; Islets of Langerhans; TNF-Related Apoptosis-Inducing Ligand

TRAIL shows potential cardioprotective activity. - Toffoli, Barbara; Bernardi, Stella; Candido, Riccardo; Zacchigna, Serena; Fabris, Bruno; Secchiero, Paola (Invest New Drugs, 2012)
Recent clinical trials carried out in patients with advanced cancer have shown that recombinant TRAIL administration is usually safe and well tolerated when used either alone or in association with chemotherapeutic drugs. Notably, anticancer chemotherapy can be associated to cardiomiopathy. We have here demonstrated that TRAIL (administrated as either recombinant soluble TRAIL or as AAV-TRAIL expression viral vector) reduced the development of cardiomyopathy in the ApoE(-/-) diabetic mouse model. These data suggest, for the first time, that therapeutically administration of TRAIL might have a cardioprotective effect.
Keywords: Animals; Apolipoproteins E; Apoptosis; Cardiotonic Agents; Diabetes Mellitus, Experimental; Diabetes Mellitus, Type 1; Diabetic Cardiomyopathies; Fibrosis; Male; Mice; Mice, Knockout; Recombinant Proteins; TNF-Related Apoptosis-Inducing Ligand

Osteoprotegerin induces morphological and functional alterations in mouse pancreatic islets. - Toffoli, Barbara; Bernardi, Stella; Candido, Riccardo; Sabato, Nicoletta; Carretta, Renzo; Corallini, Federica; Secchiero, Paola; Zauli, Giorgio; Fabris, Bruno (Mol Cell Endocrinol, 2011)
Although serum osteoprotegerin (OPG) is significantly increased in diabetic subjects, its potential role in beta cell dysfunction has not been investigated. This study aimed to assess the effect of full-length OPG administered in vivo in mice on pancreatic islet structure and function and its interaction with the renin-angiotensin system (RAS). OPG-treated mice showed increased islet monocyte/macrophage infiltration, fibrosis and apoptosis with reduction of islet function. The remodeling of islet architecture was associated with increased pancreatic expression of components of the RAS, growth factor genes (transforming growth factor β and connective tissue growth factor) and inflammatory molecules (monocyte chemotactic protein-1 and vascular adhesion molecule type 1). Prevention of these changes with improvement of insulin secretion was observed in ramipril treated animals. Our data suggest that OPG might play an important role in promoting beta cell dysfunction and that the upregulation of the local RAS represents one possible mechanism responsible for the OPG-induced beta cell dysfunction.
Keywords: Animals; Apoptosis; Blood Glucose; Blood Pressure; Body Weight; Cell Lineage; Cell Movement; Chemokine CCL2; Connective Tissue Growth Factor; Fibrosis; Gene Expression Regulation; Humans; Insulin; Islets of Langerhans; Macrophages; Mice; Monocytes; Organ Size; Osteoprotegerin; Peptidyl-Dipeptidase A; Receptor, Angiotensin, Type 1; Systole; Transforming Growth Factor beta; Vascular Cell Adhesion Molecule-1

Osteoprotegerin promotes vascular fibrosis via a TGF-β1 autocrine loop. - Toffoli, Barbara; Pickering, Raelene J; Tsorotes, Despina; Wang, Bo; Bernardi, Stella; Kantharidis, Phillip; Fabris, Bruno; Zauli, Giorgio; Secchiero, Paola; Thomas, Merlin C (Atherosclerosis, 2011)
BACKGROUND: This study was designed to evaluate the potential role of osteoprotegerin (OPG) in arterial fibrosis. METHODS: Aortic samples were analyzed after in vivo treatment of ApoE(-/-) mice with recombinant human OPG. Mouse vascular smooth muscle cells (VSMC) were exposed in vitro to recombinant OPG and analyzed for markers of inflammation and fibrosis, such as fibronectin, collagen I, III, IV and transforming growth factor-β1 (TGF-β1). Conversely, the potential modulation of endogenous OPG expression and release by VSMC was analyzed in response to different pro-atherosclerotic cytokines, TGF-β1, platelet derived growth factor (PDGF) and angiogensin II (Ang II). RESULTS: In vivo treatment with human OPG induced signs of fibrosis and up-regulated the arterial expression of TGF-β1. Consistently, in vitro treatment of VSMC with human OPG induced the expression of fibronectin, collagen type I, III, IV, metalloprotein-2 (MMP-2) and MMP-9, as well as of TGF-β1. On the other hand, exposure to recombinant TGF-β1 promoted the expression/release of endogenous OPG and mediated the increase of OPG release induced by PDGF and Ang II in VSMC. CONCLUSIONS: Taken together, these data support a pathogenic role for OPG in the development and progression of atherosclerotic lesions and suggest the existence of a vicious circle between TGF-β1 and OPG.
Keywords: Animals; Apolipoproteins E; Cell Proliferation; Collagen; Fibronectins; Fibrosis; Gene Expression Regulation; Humans; Mice; Mice, Inbred C57BL; Mice, Transgenic; Muscle, Smooth, Vascular; Myocytes, Smooth Muscle; Osteoprotegerin; Platelet-Derived Growth Factor; Transforming Growth Factor beta1

Treatment with recombinant tumor necrosis factor-related apoptosis-inducing ligand alleviates the severity of streptozotocin-induced diabetes. - Zauli, Giorgio; Toffoli, Barbara; di Iasio, Maria Grazia; Celeghini, Claudio; Fabris, Bruno; Secchiero, Paola (Diabetes, 2010)
OBJECTIVE: To evaluate the potential therapeutic effect of recombinant human tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) treatment in a model of type 1 diabetes. RESEARCH DESIGN AND METHODS: Recombinant TRAIL was added in vitro to primary human and mouse peripheral blood mononuclear cells (PBMCs) and isolated human islets to evaluate the expression of the immunoregulatory gene SOCS1. Diabetes was induced by five consecutive daily injections of low-concentration (50 mg/kg) streptozotocin (STZ) in C57 black mice (n = 24). A group of these mice (n = 12) was co-injected with recombinant TRAIL (20 microg/day) for 5 days, and the diabetic status (glycemia and body weight) was followed over time. After 6 weeks, circulating levels of insulin, TNF-alpha, and osteoprotegerin (OPG) were measured, and animals were killed to perform the histological analysis of the pancreas. RESULTS: The in vitro exposure of both PBMCs and human islets to recombinant TRAIL significantly upregulated the expression of SOCS1. With respect to STZ-treated animals, mice co-injected with STZ+TRAIL were characterized by 1) lower levels of hyperglycemia, 2) higher levels of body weight and insulinemia, 3) a partial preservation of pancreatic islets with normal morphology, and 4) a lower expression of both systemic (TNF-alpha and OPG) and pancreatic (vascular cell adhesion molecule [VCAM]-1) inflammatory markers. CONCLUSIONS: Overall, these data demonstrate that the administration of recombinant TRAIL ameliorates the severity of STZ-induced type 1 diabetes, and this effect was accompanied by the upregulation of SOCS1 expression.
Keywords: Animals; Cells, Cultured; Diabetes Mellitus, Experimental; Gene Expression; Humans; Islets of Langerhans; Leukocytes, Mononuclear; Mice; Recombinant Proteins; Suppressor of Cytokine Signaling Proteins; TNF-Related Apoptosis-Inducing Ligand